2011
DOI: 10.1038/onc.2011.403
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear transport receptor karyopherin-α2 promotes malignant breast cancer phenotypes in vitro

Abstract: Tumorigenesis and tumor progression are associated with dysfunction of the nuclear transport machinery at the level of import and export receptors (karyopherins). Recent studies have shown that the nuclear import factor karyopherin-a2 (KPNA2) is a novel prognostic marker for poor prognosis in human breast cancer. Based on the well-defined hallmarks of cancer progression, we performed a detailed in vitro characterization of the phenotypic effects caused by KPNA2 overexpression and KPNA2 silencing in benign and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
57
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(63 citation statements)
references
References 43 publications
6
57
0
Order By: Relevance
“…As shown in Fig. 5A, the subcellular localization of overexpressed KPNA2 in lung cancer cells was enriched in nucleus that is consistent with the overexpressed patterns of KPNA2 in several human cancer tissues, such as lung cancer, breast cancer, ovary cancer, bladder cancer, and esophageal squamous cell carcinoma (23)(24)(25)(26)(27)(28)30). Because of unavailability of an antibody applicable for immunofluorescence staining of endogenous E2F1 using lung cancer cells, a myc-tagged E2F1 was constructed and expressed in KPNA2-knockdown CL1-5 cells in this study.…”
Section: E2f1 Is a Novel Cargo Of Kpna2supporting
confidence: 50%
See 1 more Smart Citation
“…As shown in Fig. 5A, the subcellular localization of overexpressed KPNA2 in lung cancer cells was enriched in nucleus that is consistent with the overexpressed patterns of KPNA2 in several human cancer tissues, such as lung cancer, breast cancer, ovary cancer, bladder cancer, and esophageal squamous cell carcinoma (23)(24)(25)(26)(27)(28)30). Because of unavailability of an antibody applicable for immunofluorescence staining of endogenous E2F1 using lung cancer cells, a myc-tagged E2F1 was constructed and expressed in KPNA2-knockdown CL1-5 cells in this study.…”
Section: E2f1 Is a Novel Cargo Of Kpna2supporting
confidence: 50%
“…Recently, Noetzel et al confirmed that KPNA2 acts as a novel oncogenic factor in human breast cancer via detailed phenotypic characterization with overexpression or knockdown experiments in benign and malignant human breast cells. The group showed that up-regulation of RAC1, PCNA, p65, and OCT4 mRNA is associated with KPNA2 overexpression and proposed that these putative downstream effectors of KPNA2 contribute to the malignancy of breast cancer (30). In the current study, we employed the SILAC approach to systematically analyze global protein changes upon KPNA2 knockdown in lung cancer cells.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly we found an upregulation of karyopherin alpha 2 (KPNA2) an importin subunit involved in the recognition of the NLS complex in our experiments upon SASH1 knockdown. KPNA2 expression affects cell proliferation and migration in a wide range of human cancer cells 206,207,208 , including breast cancer 209 , moreover it is over-expressed in cancer tissues and its expression correlates with poor survival 210 . KPNA2 was also shown to be a target for p53 211 .…”
Section: Figure 16 Mass Spectrometry Identification Of Sash1 Partnermentioning
confidence: 99%
“…[34][35][36][37] Accordingly, functional analyses on cell lines have suggested an oncogenic function of KPNA2 overexpression in promoting proliferation, viability and migration of cancer cells. [4][5][6][7] Recent studies linking high KPNA2 expression to adverse clinical outcome in breast 8 and ovarian cancer, 10 melanoma, 9 and astrocytoma 11 provide further clinical evidence for a strong role of KPNA2 in cancer biology. That aberrations in molecules regulating nuclear import of tumorrelevant proteins can have a pivotal role in cancer cells is also supported by the recent observation that overexpression of Ran, another important protein of the nuclear import machinery, is linked to adverse tumor phenotype in breast and lung cancers.…”
Section: Discussionmentioning
confidence: 99%
“…3 KPNA2 is also suspected to be involved in cellular proliferation, differentiation, cell-matrix adhesion, colony formation and migration. [4][5][6][7] Increased KPNA2 expression levels, as compared with normal tissue, have been described in various malignancies including breast cancer, 8 melanoma, 9 ovarian cancer 10 and astrocytoma. 11 Upregulation of nuclear KPNA2 protein expression was described in prostate cancer tissue and KPNA2 expression levels were found to be associated with PSA recurrence after radical prostatectomy in a cohort of 707 primary prostate cancer patients.…”
mentioning
confidence: 99%